Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak Dari Wajib Pajak Badan Tahun 2016-2017 - Elvina Desideria, Ngadiman (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effect of Tax Amnesty, Tax Audit, and Taxpayer Compliance on Corporate Income Tax Revenueperiod 2016-2017. The technique used in collecting samples that is purposive sampling of corporate taxpayer that registred in KPP Pratama Gambir Empat. Result of research obtained Tax Amnesty, Tax Audit, and Taxpayer Compliancesimultanly have positive effect to Corporate Income Tax Revenue.Tax Amnesty and Taxpayer Compliancepartialy have positive effect to Corporate Income Tax Revenue and Tax Audit have no effect to Corporate Income Tax Revenue.